Warehouse management model using FEFO, 5s, and chaotic storage to improve product loading times in small- and medium-sized non-metallic mining companies - Espinoza-Camino, P. (2020)
This article addresses one of the main problems faced by small- and medium-sized business in the non-metallic mining sector in Peru. These companies own warehouses and face the major problem of failing to deliver orders correctly and in a timely manner. This problem usually occurs when the business grows from a small- to medium-sized company in a short span of time; this situation leads to new processes within warehouses that are mostly not standardized. Besides, facilities are no longer optimal in space and the workers are not properly trained. The case study shows that the orders were not delivered on time due to factors such as lack of product identification, although the products have an expiration date and a warehouse without signaling and surrounded by traffic. To tackle this situation, a labeling process has been designed for the products, an adequate distribution technique is used in the warehouse through a newly designed warehouse layout, and a First Expired, First Out system has been implemented. Similarly, the design is accompanied by the 5s tool to provide a basis for order and continuous improvement. The results show that deliveries with delays were reduced from 38% to 10%. These results show that companies can grow rapidly and maintain quality of service through orderly management.